Role of the circadian system in cardiovascular disease - Saurabh S. Thosar; Matthew P. Butler; Steven A. Shea (The Journal of Clinical Investigation, 2018)
All species organize behaviors to optimally match daily changes in the environment, leading to pronounced activity/rest cycles that track the light/dark cycle. Endogenous, approximately 24-hour circadian rhythms in the brain, autonomic nervous system, heart, and vasculature prepare the cardiovascular system for optimal function during these anticipated behavioral cycles. Cardiovascular circadian rhythms, however, may be a double-edged sword. The normal amplified responses in the morning may aid the transition from sleep to activity, but such exaggerated responses are potentially perilous in individuals susceptible to adverse cardiovascular events. Indeed, the occurrence of stroke, myocardial infarction, and sudden cardiac death all have daily patterns, striking most frequently in the morning. Furthermore, chronic disruptions of the circadian clock, as with night-shift work, contribute to increased cardiovascular risk. Here we highlight the importance of the circadian system to normal cardiovascular function and to cardiovascular disease, and identify opportunities for optimizing timing of medications in cardiovascular disease.